Physical, Electrical and Optical Properties of F/Sb Codoped SnO2 Synthesized Via Sonochemical Process. Issue 1 (2nd January 2016) - Noonuruk, R.; Mekprasart, W.; Vittayakorn, N.; Sritharathikhun, J.; Pecharapa, W.
Abstract : F/Sb-codoped SnO2 nanoparticles were synthesized via sonochemical process using stannic chloride pentahydrate (SnCl4 ·5H2 O) as host precursor while antimony(III) chloride (SbCl3 ) and ammonium fluoride (NH4 F) were chosen as Sb and F dopant precursors, respectively. Their physical properties and morphologies were investigated using X-ray diffraction, Raman spectroscopy, X-ray photoelectron spectroscopy and transmission electron microscope while their electrical and optical properties were investigated by Hall measurement and diffuse reflectance spectroscopy. As-synthesized powder of polycrystalline phase SnO2 nanoparticles can be obtained by one-step sonochemical process and its crystallinity can be improved by calcination process. The formation of crystalline phase of SnO2 is assisted by cavitation effect provided by intense ultrasonic radiation via rapid collision. The characterization results disclose that Sb dopant has strong influence on both physical and electrical properties while F dopant provide considerable effect on electrical property of the samples. It is noticed that the codoping of both elements with certain contents can significantly heighten its electrical conductivity.